Evaluation of Anti-urolithiatic Potential of Leaves of Alstonia scholaris and its Isolated Pentacyclic Triterpenoids in Ethylene Glycol-induced Renal Calculi Rat Model - S, Zehra; MM, Sanaye (Indian Journal of Pharmaceutical Education and Research, 2021)
Introduction: Urolithiasis has afflicted human race since the days of yore. Conventional treatment acts only on associated ailments whereas pharmacologically active phytoconstituents derived from plants are reported to possess lithotriptic as well as anti-urolithiatic effect, thus herbal sources need to be scientifically explored. Present study was aimed to evaluate anti-urolithiatic potential of leaves of Alstonia scholaris and its isolated pentacyclic triterpenoids: lupeol and ursolic acid in ethylene glycolinduced renal calculi rat model. Materials and Methods: Leaves of Alstonia scholaris were extracted with various solvents, amount of triterpenoids in each extract was quantified using HPTLC. Extract which had higher amount of triterpenoid was evaluated for its anti-urolithiatic effect. Albino wistar rats of either sex were divided into 6 groups. All groups except vehicle were fed with 0.75%v/v of ethylene glycol for 28 days. Treatment with standard cystone, low and high dose of extract and pentacyclic triterpenoids were given to respective groups from 4th-28th day of study. On 28th day, serum creatinine, uric acid, BUN, TNF-α, IL-6 and urinary electrolyte levels were estimated. Kidneys were isolated, one was used for histopathological study and other for antioxidant assays. Results and Discussion: Histopathological examination of kidneys revealed destructed morphology due to deposition of large polymorphic crystals and cystic dilatation of tubules. Whereas treatment with extract and its pentacyclic triterpenoids prevented renal damage and deposition of crystals. Perturbations in levels of nitrogenous wastes, inflammatory mediators and urinary electrolytes were also prevented. Alstonia scholaris rich in triterpenoid significantly arrested associated oxidative stress and inflammation thus preventing formation of renal calculi. Conclusion: Leaves of Alstonia scholaris and pentacyclic triterpenoids isolated from them demonstrates potent herbal remedy for treatment of urolithiasis.
Keywords: Alstonia scholaris; Anti-inflammatory; Lupeol; Oxidative stress; Ursolic acid; Urolithiasis